(untitled) (Swiss Medical Weekly, 2010)
Background: Domestic violence is considered one of the most common forms of gender-related violence, and various studies estimate that between 10 and 35% of women experience domestic violence at some point in their lives. Nevertheless, it is a frequently neglected problem in crisis intervention centres, emergency wards, and obstetrics and gynaecological emergency rooms. This paper contributes to clarifying the definition, epidemiology, risk factors and consequences of domestic violence against women as well as the psychopathological profile of victims with a focus on Central European countries. Although different studies on domestic violence report different risk factors, such as younger age, being unmarried, lower education, violence experienced during childhood and alcohol/drug abuse of the partner or the victim herself, the results show no overall consistency. There seems to be neither a definite risk profile nor a specific association with a psychopathological profile. Women who have been victimised find it hard to share their experiences and seek help. It is often difficult for medical personnel who encounter these women to recognise violence and discuss this problem with them, just as it is difficult to offer adequate help. Medical personnel should be alerted to this subject and prepare guidelines for the further management and treatment of abused women. Infor-mation and support for medical staff can help to identify domestic violence, and encourage communication about this problem, thereby leading to a better and more efficient use of available services and resources.